Tensile Recovery in Nylon 6/Modified Butyl-Rubber Blend System Consisting of Rubber Particles Distributed in a Nylon Matrix - KAIDO, Hiroyuki; ENOMOTO, Tatsuya; SAWAI, Daisuke; HARA, Yuichi; KANAMOTO, Tetsuo; MOROOKA, Naoyuki; SOEDA, Yoshihiro (KOBUNSHI RONBUNSHU, 2005)
The effect of morphology on the tensile recovery was studied for a series of blends of nylon 6 (PA6) and a brominated poly (isobutylene-co-p-methylstyrene) copolymer (BIMS rubber) having wide variations in composition and morphology. To modify the morphology of the simple blends consisting of the two components, we added a small amount of sulfur (0.5 wt% of the rubber component) and kneaded the mixtures by two different manners at around 250°C. Microscopic observations of a simple blend of PA6/BIMS=60/40 revealed that rubber particles of a diameter=0.2-0.8μm were uniformly dispersed in the continuous PA6 matrix. However, upon kneading of sulfur, the rubber particles aggregated to form a large domain (1-5μm) with an irregular shape; such domains were distributed in the PA6 matrix. Closer inspections of the transmission electron micrographs revealed that small domains of the PA6 component were included within a larger rubber domain. Such blends with heterogeneous morphology showed a lower dynamic Young's modulus and a superior strain recovery compared to those with uniformly dispersed rubber particles. It was found that the tensile set for a series of the blends could be represented by a unique function of the dynamic Young's modulus, independently of the blend composition.